Parental warmth buffers the effect of socioeconomic status on resilience during late childhood: evidence from a nationally representative birth cohort - Yu, Meryl (2024)
According to the Family Stress Model (FSM), chronic exposure to economic hardships bolsters risks of maladaptive development in children via the mechanism of parenting. Specifically, in face of later adversities, children of lowersocioeconomic status (SES) are found to exhibit less resilience than well-off peers, but the exact parenting mechanisms remain undiscerned. Guided by the FSM, we examine parental care and parental overprotection as candidate mediators in the relationship linking SES to resilience in late childhood. We used longitudinal data from 293 children-mother dyads (48% girls) from Singapore’s largest birth cohort. A composite SES score was derived by averaging the standardized scores of maternal and paternal education and household income, reported by mothers at recruitment. Children reported resilience at age 10.5 with Connor-Davidson Resilience Scale, and parental care and overprotection at age 8.5 with Parental Bonding Instrument. Linear regression revealed that SES was positively predictive of resilience, B=4.04(1.10), p<.001, controlling for child gender. Parallel mediation analysis with PROCESS (Hayes, 2017) and 10,000 bootstrap samples was run to test indirect effects of SES on resilience through parental care and overprotection, controlling for child gender. Parental care was a significant mediator, B=1.98, SE=0.56, 95%CI[0.95, 3.18], but parental overprotection was not, B=0.18, SE=0.21, 95%CI[-0.21,0.67]. Total mediation effect was significant, B=2.17, SE=0.58, 95%CI[1.10, 3.38]. SES was no longer a significant predictor when mediators were added, B=2.08, SE=1.20, p=.08, suggesting full mediation. We offer empirical evidence that parental care is a salient pathway linking SES to child resilience.